2017
DOI: 10.1002/app.45006
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid‐modified graphene/poly(vinyl alcohol) composite with enhanced properties

Abstract: How to preserve the structure integrity of graphene while enhance its dispersion and compatibility in matrix attracts the attention of researchers in graphene/polymer nanocomposite field. In this paper, methacryloxyethyltrimethyl ammonium chloride (DMC), a kind of ionic liquids, was first used to non‐covalently functionalize graphene in the process of graphene oxide (GO) reduction. The as‐modified graphene (DMC‐rGO) was further incorporated into poly(vinyl alcohol) (PVA) matrix by solution casting technique to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
(45 reference statements)
0
12
0
1
Order By: Relevance
“…[ 134 ] Similar results were obtained by incorporating ionic liquid modified graphene into poly(vinyl alcohol) (PVA) by solution casting technique. [ 135 ] Using this coupling agent, the structure integrity of graphene could be preserved and the aggregation was relieved. With a low loading amount of 2 wt%, marked enhancements in mechanical properties, thermal stabilities and electrical conductivities were achieved.…”
Section: Other Typical Applications Of Cation–π Interactions In Graphmentioning
confidence: 99%
“…[ 134 ] Similar results were obtained by incorporating ionic liquid modified graphene into poly(vinyl alcohol) (PVA) by solution casting technique. [ 135 ] Using this coupling agent, the structure integrity of graphene could be preserved and the aggregation was relieved. With a low loading amount of 2 wt%, marked enhancements in mechanical properties, thermal stabilities and electrical conductivities were achieved.…”
Section: Other Typical Applications Of Cation–π Interactions In Graphmentioning
confidence: 99%
“…ILs are known to interact with the graphene by cation–π stacking and π–π interactions which prevent reaggregation of graphene sheets [9,10]. Their ability to improve the dispersion of graphene in several thermoplastic matrices has been demonstrated [7,9,11,12,13,14]. Therefore, it can be concluded that, although not clearly detected by TEM, the modification of GR with IL leads to the enhanced dispersion of the nanofiller, which, in turn, gives rise to a significantly lower electrical percolation threshold in the bTPU/GR-IL NCs than in the bTPU/GR NCs.…”
Section: Resultsmentioning
confidence: 99%
“…ILs are believed to interact with graphene by cation–π stacking and π–π interactions which prevent the reaggregation of graphene sheets while preserving the electronic structure of the graphene and its intrinsic properties [9,10]. As a result, ILs have been successfully used as dispersing agents for graphene in several thermoplastic matrices, including poly(vinyl alcohol) [11], a copolyamide [12], polylactide [9], polystyrene [13], poly(methyl methacrylate) [14], and polyvinylidene fluoride [7].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of ILs with polymers is expected to further extend their applicability. Novel functions [4][5][6][7] and physical properties [8][9][10][11][12][13][14] are reported in polymer/IL systems. For example, polymer gels swollen by ILs are excellent gel polymer electrolytes (GPEs) with the properties of ILs, which includes great electrochemical stability across a large window.…”
Section: Introductionmentioning
confidence: 99%